Investigation of physiological responses and leaf morphological traits of wheat genotypes with contrasting drought stress tolerance - Deák, Csilla (Acta Biologica Szegediensis, 2011)
Drought sensitive Cappelle Desprez, GK Élet and drougt tolerant Plainsman V, Mv Emese winter wheat (Triticum aestivum) genotypes were subjected to water deprivation at anthesis. Gas exchange measurements showed depletion of internal CO2 in the leaves of the tolerant but not in the sensitive cultivars. Tolerant genotypes had lower stomatal density and significantly smaller leaves than the sensitive ones. The potential contribution of these traits to drought tolerance is discussed.